The Role of Ethical Leadership in Online Sustainability Reporting: A Study on Malaysia - Rahim, Nazahah; Biggs, David; Aly, Doaa (2017)
Stakeholders demand transparency through better information disclosure to curtail corporate scandals and to regain trust. The answer is online sustainability reporting that can provide timely information and meets stakeholders’ demands for greater speed and a greater volume of information disclosure.The objective of this study is to investigate the current level of online sustainability reporting among public listed companies in Malaysia and to explain any variations in online sustainability reporting, using ethical leadership behaviours as the explanatory factors. A disclosure index, which included 60 CSR/sustainability items grouped according to four dimensions-community, workplace, marketplace and environment is used. The explanatory variables are extracted from a questionnaire survey, where univariate and multivariate analyses are employed.The items in the questionnaire are based on the Ethical Leadership at Work (ELW) scale developed by Kalshoven et al. (2011)which focuses on respondents’ opinion on ethical leadership of their supervisors at their respective companies. The results indicate that leaders’ ethical guidance, concern about sustainability and role clarification are affecting the amount of CSR information disclosed on Malaysian companies’ websites.This study provides new insight for corporate leaders, academics and policymakers on how the behaviours of leaders, who are key corporate players, can impact on the setting of sustainability goals and enhance accountability through online disclosure.Limited studies have examined leadership related variables as a determinant of disclosing sustainability information online.The empirical evidence of this study provides support for human-related factors, which has never been discovered before.